Paroxysmal Ocular Downward Deviation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Paroxysmal ocular downward deviation in 13 children with spastic quadriplegia, mental retardation and cortical visual impairment is reported from the Department of Pediatric Neurology, Seirei-Mikatabara General Hospital, Hamamatsu, Shizuoka, Japan.